Analisis Pengelolaan Aspek Keuangan dalam Mendukung Keberlanjutan Usaha pada UMKM Telor Asin Vallen Rasa - Baniarif Riski Lubab; Naufal Nur Fadil; Makmur Sujarwo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting economic growth and improving community welfare. One of the key factors determining business sustainability is effective financial management. Proper financial management enables MSME owners to manage capital, control cash flow, and make appropriate business decisions. This study aims to analyze financial management practices in supporting business sustainability at Vallen Rasa Salted Egg MSME. This research employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that Vallen Rasa Salted Egg MSME has implemented financial management practices by separating business and personal finances, maintaining bookkeeping records, and utilizing a financial recording application. However, in practice, financial records are more frequently maintained manually in notebooks and are not consistently recorded. In addition, limited financial knowledge and skills, as well as less-than-optimal financial planning, remain major challenges in supporting effective business decision-making. Nevertheless, the financial management practices that have been implemented have contributed to maintaining business operations and supporting the sustainability of the enterprise. Therefore, it is necessary to enhance financial management competencies, optimize the use of financial recording applications, and develop more systematic financial planning to improve business management effectiveness and sustainability.